2020
DOI: 10.1136/bmjgh-2020-002794
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of secondary transmission of SARS-CoV-2 in households by face mask use, disinfection and social distancing: a cohort study in Beijing, China

Abstract: IntroductionTransmission of COVID-19 within families and close contacts accounts for the majority of epidemic growth. Community mask wearing, hand washing and social distancing are thought to be effective but there is little evidence to inform or support community members on COVID-19 risk reduction within families.MethodsA retrospective cohort study of 335 people in 124 families and with at least one laboratory confirmed COVID-19 case was conducted from 28 February to 27 March 2020, in Beijing, China. The outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
471
8
10

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 467 publications
(549 citation statements)
references
References 11 publications
(2 reference statements)
30
471
8
10
Order By: Relevance
“…Human pathogenic corona viruses, which include SARS-CoV-2 that is responsible for COVID-19, bind to their target cells through the angiotensin-converting enzyme 2 (ACE2) receptor, which is expressed by epithelial cells of the lung, intestine, kidney, and blood vessels [21]. It is possible that PM 2.5 may induce the elevation of ACE2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Human pathogenic corona viruses, which include SARS-CoV-2 that is responsible for COVID-19, bind to their target cells through the angiotensin-converting enzyme 2 (ACE2) receptor, which is expressed by epithelial cells of the lung, intestine, kidney, and blood vessels [21]. It is possible that PM 2.5 may induce the elevation of ACE2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…A study of Chinese families in Beijing, published in BMJ Global Health ,1 found that wearing face masks at home may reduce the spread of covid-19 infection among family members living in the same household, but only before symptoms develop. A face mask worn before symptoms started was 79% effective, and disinfection 77% effective, at stopping the virus from being passed on, the study found.…”
Section: Public Healthmentioning
confidence: 99%
“…As anticipated by the guidance provided by the U.S. Centers for Disease Control and Prevention (CDC) 1 , the World Health Organization (WHO) 2,3 , and other regional centers for disease prevention and control, the infection prevention and control (IPAC) strategies of most utility in dealing with the SARS-CoV-2 (COVID- 19) pandemic appear to be social distancing, the wearing of face masks, and the use of microbicides for hand hygiene and for sanitization of high-touch environmental surfaces (HITES) 4 . The latter include, but are not limited to, the toilet, bathroom and kitchen sinks, food preparation surfaces, door knobs, toys, desk tops, coins and paper currency, cell phones and other small electronic devices, automatic teller machines, and shopping carts, etc.)…”
Section: Introductionmentioning
confidence: 99%